2015
DOI: 10.1158/2326-6066.cir-14-0036
|View full text |Cite
|
Sign up to set email alerts
|

Tasquinimod Modulates Suppressive Myeloid Cells and Enhances Cancer Immunotherapies in Murine Models

Abstract: A major barrier for cancer immunotherapy is the presence of suppressive cell populations in cancer patients, such as myeloid-derived suppressor cells (MDSC) and tumor-associated macrophages (TAM), which contribute to the immunosuppressive microenvironment that promotes tumor growth and metastasis. Tasquinimod is a novel antitumor agent that is currently at an advanced stage of clinical development for treatment of castration-resistant prostate cancer. A target of tasquinimod is the inflammatory protein S100A9,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 51 publications
4
72
0
Order By: Relevance
“…For example, tasquinimod binds to and inhibits signaling by S100A9, a molecule known to be important for accumulation and activation of MDSCs (126). In murine prostate tumor models, tasquinimod treatment led to decreased MDSC numbers and functions, and increased antitumor responses (137). This treatment was well tolerated, slowed tumor progression, and increased survival in phase II trials in castrate-resistant prostate cancer patients (119).…”
Section: Direct Targeting Of Mdscs In Vivomentioning
confidence: 99%
“…For example, tasquinimod binds to and inhibits signaling by S100A9, a molecule known to be important for accumulation and activation of MDSCs (126). In murine prostate tumor models, tasquinimod treatment led to decreased MDSC numbers and functions, and increased antitumor responses (137). This treatment was well tolerated, slowed tumor progression, and increased survival in phase II trials in castrate-resistant prostate cancer patients (119).…”
Section: Direct Targeting Of Mdscs In Vivomentioning
confidence: 99%
“…In the tumor, these cells appear as tumor-associated M2 macrophages or infiltrating monocytic/granulocytic cells. Recent studies with tasquinimod, another quinoline compound, showed that tasquinimod triggers a polarization of macrophages from a M2 to a M1 phenotype in the tumour microenvironment [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Tasquinimod, a novel antitumor agent has been reported to prolong the progression-free survival of human castration-resistant prostate cancer patients [182]. Tasquinimod enhanced the effectiveness of immunotherapy, inhibited the accumulation of Ly6C+ MDSCs and CD206+ M2-like TAMs via targeting S100A9, furthermore CD11b+ myeloid cells showed less ArgI and iNOS expression which resulted in significantly reduced tumor growth in murine models of prostate cancer and melanoma [183] (Table 3). …”
Section: Therapeutic Interventions Targeting Tams and Mdscs Tuninmentioning
confidence: 99%